2019
DOI: 10.1016/j.radi.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional work in early detection of breast cancer: An integrative review

Abstract: a b s t r a c tObjectives: To identify the roles of health care staff in interprofessional work related to breast cancer detection and diagnosis.Key findings: A comprehensive search was performed using PICO to support inclusion and exclusion criteria. A shortened version of the STROBE checklist ensured evaluation of the studies. 21 included studies resulted in three main categories describing the role of health care professionals; (1) Communicating breast cancer awareness; (2) The Professional's tasks; (3) Eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
1
0
1
Order By: Relevance
“…16,26 This is one of the reasons why multiprofessional collaboration in breast cancer diagnostics and care is extremely important. 3,32 Women in our study reported feeling happy about smooth chemotherapy, endocrine and biological, radiotherapy treatments. They also reported about the less positive experiences regarding the side effects and treatment.…”
Section: Women's Experiences Associated With Breast Cancer Treatment ...mentioning
confidence: 67%
“…16,26 This is one of the reasons why multiprofessional collaboration in breast cancer diagnostics and care is extremely important. 3,32 Women in our study reported feeling happy about smooth chemotherapy, endocrine and biological, radiotherapy treatments. They also reported about the less positive experiences regarding the side effects and treatment.…”
Section: Women's Experiences Associated With Breast Cancer Treatment ...mentioning
confidence: 67%
“…Manfaat kolaborasi interprofesi dapat memperkuat setiap profesi karena kekhususan masing-masing tugas dapat terlihat (Strøm et al, 2019). Tiga komponen utama pada model kolaborasi yaitu lingkungan (kepemimpinan, dukungan secara administratif untuk koordinasi), struktur (tujuan, peran dan tanggungjawab), juga proses (aktivitas berbagi) (Gagliardi et al, 2011).…”
Section: Pembahasanunclassified